JUAL BELI ONLINE BERBASIS MEDIA SOSIAL DALAM PERSPEKTIF EKONOMI ISLAM - Aswawi, Nurafiah (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2023)
This research is entitled Social Media-Based Online Buying and Selling in the Perspective of Islamic Economics. The purpose of this research is to find out Social Media-Based Online Buying and Selling in the Perspective of Islamic Economics. One of the phenomena of mu'amalah in the economic field is buying and selling transactions using electronic media, technological developments have spurred changes in individual habits, including one of them in terms of buying and selling transactions. The research method focuses on the discussion of the function of money in the perspective of Islamic Economics. This research is a type of library research, namely research conducted using literature or literature from previous studies. The results of the study explain that in the past what was meant by buying and selling transactions had to be done face to face where there was a direct transfer of goods from the seller to the buyer, namely the buyer had to meet the seller in the real market. Currently, it has transitioned to an era where transactions are no longer carried out face-to-face, but through online media. In the viewpoint of fiqh on-line buying and selling is allowed in Islam in accordance with the fiqh principle "Al-ashl fi mu'amalah al -ibahah, illa idza ma dalla al-dalil ala khilafihi, as long as in the process there are no elements that are contrary to Islam such as fraud, uncertainty and usury.